2013
DOI: 10.1002/mrm.24687
|View full text |Cite
|
Sign up to set email alerts
|

Fe(III) distribution varies substantially within and between atherosclerotic plaques

Abstract: Objective: Vulnerable atherosclerotic plaques are structurally weak and prone to rupture, presumably due to local oxidative stress. Redox active iron is linked to oxidative stress and the aim of this study was to investigate the distribution of Fe(III) in carotid plaques and its relation to vulnerability for rupture.Methods: Atherosclerotic plaques from ten patients (3 asymptomatic and 7 symptomatic) were investigated. Plaque vulnerability was classified using ultrasound and immunohistochemistry and correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…[90] In addition, hepcidin levels might be related with the severity of plaque destabilization, which is in accordance with higher levels of iron observed in the plaques of symptomatic patients compared with non-symptomatic patients. 97 Interestingly, levels of iron protein importers, such as TFR1, are also increased in plaques of symptomatic patients and are associated with plaque instability. 98 In addition, it has been suggested that HH patients seem to be protected from atherosclerosis, which can be explained by the lower levels of serum hepcidin observed in this condition.…”
Section: Hepcidin In Cardiac Homeostasismentioning
confidence: 99%
“…[90] In addition, hepcidin levels might be related with the severity of plaque destabilization, which is in accordance with higher levels of iron observed in the plaques of symptomatic patients compared with non-symptomatic patients. 97 Interestingly, levels of iron protein importers, such as TFR1, are also increased in plaques of symptomatic patients and are associated with plaque instability. 98 In addition, it has been suggested that HH patients seem to be protected from atherosclerosis, which can be explained by the lower levels of serum hepcidin observed in this condition.…”
Section: Hepcidin In Cardiac Homeostasismentioning
confidence: 99%
“…Plaques from symptomatic patients showed higher iron concentrations, signs of cap rupture and increased cap macrophage activity compared with asymptomatic plaques (Gustafsson et al, 2013). This suggests that the presence of iron in carotid plaques positively correlates with plaque vulnerability for rupture.…”
Section: Altered Iron Homeostasis and Atherosclerosis: Epidemiologicamentioning
confidence: 99%
“…We recently performed an EPR study to assess data concerning differences in iron content as a sign of hemorrhage in clinical silent plaques as compared to plaques provoking neurological symptoms . We showed that the Fe(III) distribution varies substantially within atherosclerotic plaques and that plaques from symptomatic patients had significantly higher concentrations of Fe(III), as well as signs of cap rupture and increased cap macrophage activity . Although the method for tissue preparation differed, the previous iron quantification study was based on paraffin embedded and formalin fixed tissue, an increase in cap foamy macrophages was also seen in the currently investigated plaque based on fresh, rapidly frozen sections.…”
Section: Discussionmentioning
confidence: 95%
“…EPR can also be used to quantify Fe(III) in ex vivo atherosclerotic plaques in addition to studies of oxidative stress. We recently performed an EPR study to assess data concerning differences in iron content as a sign of hemorrhage in clinical silent plaques as compared to plaques provoking neurological symptoms . We showed that the Fe(III) distribution varies substantially within atherosclerotic plaques and that plaques from symptomatic patients had significantly higher concentrations of Fe(III), as well as signs of cap rupture and increased cap macrophage activity .…”
Section: Discussionmentioning
confidence: 99%